An investigation of the introduction of water-soluble polysaccharides calamus root (Acorus calamus L.) effect on the experimental animals functions - A. M. Gurieyv; M. V. Belousov; R. R. Akhmedzhanov; M. S. Yusubov; A. A. Churin; G. V. Karpova (Бюллетень сибирской медицины, 2010)
An investigation has been performed as to the effect of a long-term parenteral introduction of the sum of water-soluble polysaccharides (WSPS) calamus root (Acorus calamus L.) extracted by means of the in-house technology on the functions of experimental animals. As it follows from the results of the experiments, the intragastric introduction of the WSPS to rats in the doses of 20, 100, and 200 mg/kg during a three-month term and the intravenous introduction to rabbits in the doses of 25 and 50 mg/kg during a one-month term do not lead to the death of the animals or to any pathological changes in their general condition, the dynamics of the general weight, or the functional activity of the investigated internal organs and systems.